Estimation of seasonal, additive and non‑additive genetic components in diploid banana (Musa spp.) - Akech, V.; Bayo, S.J.; Bengtsson, T.; Ortiz, R.; Swennen, R.; Gezan, S.; Vuylsteke, M.; Brown, A. (2025)
This study focuses on improving the efficiency of breeding diploid bananas for important traits such as yield, fruit size and weight. Partitioning genetic variance into additive and non-additive components is crucial. This is challenging in most commonly available family structures in banana breeding due to reduced fertility and ploidy complications. However, the availability of replicated clones of full-sib progeny allows greater insight into the genetics of perennial diploid bananas. Clones of nine full-sib families, generated through a factorial mating design consisting of six diploid parthenocarpic female and two wild diploid male banana (Musa spp.) parents, were evaluated at the International Institute of Tropical Agriculture in Arusha. Data were collected over two harvests (plant crop and first ratoon) to provide a better understanding of the genetic architecture of key traits and their seasonal influence. Pedigree-based models were fitted to the data to estimate additive, dominance, epistatic variance components, and seasonal effects. Additive variance was the major source of genetic variance for most traits. Dominance and epistatic variances were non-significant for most traits, with a few exceptions. Broad-sense and narrow-sense heritability estimates were high for most traits. A significant positive correlation was found between yield traits and between the plant and first ratoon crops for yield traits, which will help accelerate selection and improve genetic gains. These results enhance our understanding of the genetic architecture of quantitative traits in bananas and lay a foundation for further study in this almost recalcitrant to crossbreeding but important crop.